(untitled) (Nigerian Dental Journal, 2023)
Ameloblastomas are benign tumors of odontogenic epithelium. They are locally aggressive with tendency to recur and sometimes with metastatic behavior. Recurrences often occur due to incomplete treatment and they can occur at difficult sites such as temporal and infratemporal fossa. Recurrences in the temporal area are very rare and are related to the type of primary treatment. AIM: This literature review aims to answer the question on how common recurrent ameloblastoma entends to the infratemporal fossa and how this is related to the site of the primary lesion. METHODS; Web search for case reports, case series of ameloblatoma with temporal, infratemporal extension, published in the English literature was carried out. Search results were further scrutinized for age, sex, location of lesion, histology, treatment modalities and recurrence following the adopted treatment modalities and treatment outcome. RESULT; A total 15 full length articles were included in this study. Twelve were case reports and 3 were case series. Of 28 patients with ameloblastoma in the articles, only 22 were recorded to have presented with ameloblastoma with infratemporal or temporal fossa involvement. All the cases of ameloblastoma involving the infratemporal/temporal fossa were recurrent tumors and the average time from first surgical intervention to recurrence was 11.36 years. Most of the primary cases were seen in the mandible (73%) with body/ramus region being the commonest location. Only 5cases were reported to be primarily maxillary ameloblastoma. CONCLUSION; This review has shown that temporal/infratemporal extension of ameloblastoma occurs commonly with recurrent lesions, although the overall reported incidence is relatively low. Aggressive primary tumor resection, especially for extensive mandibular lesions may be key to preventing this tumor extension.